Chronic pain and gait analysis in dogs with degenerative hip joint disease treated with repeated intra-articular injections of platelet-rich plasma or allogeneic adipose-derived stem cells - Okamoto-Okubo, Celina Emiko [UNESP] (2021)
This prospective, comparative, randomized, horizontal, and double-blind clinical study investigated the clinical efficacy of leucocyte-poor platelet-rich plasma (PRP, n=8) or allogeneic adipose-derived stem cells (ADSC, n=8) in dogs with bilateral degenerative hip joint disease (DHJD). Sixteen dogs were treated with two intra-articular injections of PRP or ADSCs, within a 30-day interval. The Canine Brief Pain Inventory (CBPI), the Helsinki Chronic Pain Index (HCPI), and Visual Analogue Scales for pain (VAS-pain) and locomotion (VAS-loc) were assessed by the dog owners. Analysis-of-gait using a force plate, response to palpation (VAS-palp), and the descriptive numerical scale for pain (DNS) were measured by a veterinarian. The assessments were performed before (baseline), 30 and 60 days after the first treatment. Data were analyzed using the unpaired t test, paired Wilcoxon test, Fisher’s exact test, and Mann-Whitney and Friedman tests (P<0.05). Compared with baseline HCPI, CBPI, VAS-pain, and VAS-palp scores reduced 41%, 52%, 51%, and 48% (P=0.0001–0.03) at 60 days in the ADSC group. In PRP-treated dogs, CBPI, VAS-loc, and DNS scores decreased by 43%, 43%, and 33% at 60 days, respectively (P=0.0003–0.011). Based on CBPI data, the rate of success at 60 days was 75% and 25% in the ADSC and PRP groups (P=0.13), respectively. Both therapies were apparently safe and effective to reduce chronic pain in dogs with bilateral DHJD during a 60-day period. However, a trend towards greater improvement was provided by the ADSC treatment.